Sequential Percutaneous LAA Ligation and Pulmonary Vein Isolation in Patients with Persistent AF: Initial Results of a Feasibility Study. (29th April 2015) - BADHWAR, NITISH; LAKKIREDDY, DHANUNJAYA; KAWAMURA, MITSUHARU; HAN, FREDERICK T.; IYER, SIVARAMAN K.; MOYERS, BRIAN S.; DEWLAND, THOMAS A.; WOODS, CHRIS; FERRELL, RYAN; NATH, JAYANT; EARNEST, MATHEW; LEE, RANDALL J.
LAA Ligation and Pulmonary Vein Isolation Introduction Left atrial appendage (LAA) ligation results in LAA electrical isolation and a decrease in atrial fibrillation (AF) burden. This study assessed the feasibility of combined percutaneous LAA ligation and pulmonary vein isolation (PVI) in patients with persistent AF. Methods and Results A total of 22 patients with persistent AF underwent LAA ligation with the LARIAT device followed by PVI. PVI was confirmed with the demonstration of both entrance and exit block. Patients (n = 10) in sinus rhythm pre‐ and post‐LAA ligation underwent P‐wave analysis. Monitoring for AF was performed at 1, 3, and 6 months postablation. LAA ligation was successful in 21 of 22 (95%) patients. The procedure was aborted in one patient due to pericardial adhesions. PVI was performed in 20 of 21 patients. One patient converted to atrial flutter with a controlled ventricular response after LAA ligation and refused subsequent PVI. Demonstration of entrance and exit block was achieved in 19 of 20 patients. At 3 months, 13 of 19 (68.4%) patients were in sinus rhythm. Four patients underwent a second PVI. At 6 months, 15 of 20 (75%) patients were in sinus rhythm. There was a significant decrease in P‐wave duration and P‐wave dispersion after LAA ligation. Complications with LAA ligation included pericarditis, a delayed pleural effusion, and a late pericardial effusion. Conclusions Staged LAA ligation and PVI is feasible and decreases P‐wave dispersion. Randomized studies are needed to assess the efficacy of LAA ligation as adjunctive therapy to PVI for maintaining sinus rhythm in patients with persistent AF.